2003
DOI: 10.2527/2003.8182032x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating processing temperature and feeding value of extruded-expelled soybean meal on nursery and finishing pig growth performance1,2

Abstract: We conducted two experiments comparing the use of extruded-expelled soybean meal (EESoy) to solvent-extracted soybean meal (SBM) in swine diets. In Exp. 1, the objective was to determine the optimal processing temperature of EESoy for nursery pig growth performance. Pigs (n = 330, 13.2 +/- 2.3 kg of BW) were fed a control diet containing SBM with added fat or one of five diets containing EESoy extruded at 143.3, 148.9, 154.4, 160.0, or 165.6 degrees C. All diets were formulated on an equal apparent digestible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…This results in a product with greater fat content (~7 vs. <1% fat) than conventionally pro-cessed solvent-extracted soybean meal (Woodworth et al, 2001). Like the results herein, Webster et al (2003) found improved G:F of pigs fed diets containing EESM compared with those fed a control diet.…”
Section: Effects On Growth Performancecontrasting
confidence: 46%
See 1 more Smart Citation
“…This results in a product with greater fat content (~7 vs. <1% fat) than conventionally pro-cessed solvent-extracted soybean meal (Woodworth et al, 2001). Like the results herein, Webster et al (2003) found improved G:F of pigs fed diets containing EESM compared with those fed a control diet.…”
Section: Effects On Growth Performancecontrasting
confidence: 46%
“…Alternative feed ingredients such as extruded expelled soybean meal (EESM) and dried distillers grains with solubles (DDGS) have been successfully included in swine diets (Webster et al, 2003;Stein and Shurson, 2009). However, both feedstuffs increase the amount of unsaturated fats in the diet and, therefore, may influence carcass fat quality because carcass fat composition is affected by dietary fatty acids (Brooks, 1971;Wood, 1984;Gatlin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been adopted as an alternative means of producing soybean meal and other oilseed meal and oils for human consumption or the livestock industry, or both (Webster et al, 2003). The extruder-expeller process results in a product (DESBM) that has a higher fat content compared with solventextracted soybean meal (Webster et al, 2003;Opapeju et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been adopted as an alternative means of producing soybean meal and other oilseed meal and oils for human consumption or the livestock industry, or both (Webster et al, 2003). The extruder-expeller process results in a product (DESBM) that has a higher fat content compared with solventextracted soybean meal (Webster et al, 2003;Opapeju et al, 2006). A co-extruded blend of canola seed and pea (50:50 wt/wt) has been evaluated as a potential high-energy and protein ingredient for poultry and swine in Western Canada (Golian et al, 2007;Kiarie and Nyachoti, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ESBM also showed higher soluble dietary fibre content, better water and oil retention capacities, and improved swelling capacity (Jing & Chi, ). The fat content is higher in ESBM compared with solvent‐extracted SBM, indicating a promising application prospects for DSMB in livestock and poultry industries (Opapeju, Golian, Nyachoti, & Campbell, ; Webster et al, ).…”
Section: Introductionmentioning
confidence: 99%